WTO as an international organization - "Krueger,O.Anne (ed.)" (New Delhi, 1999)
The World Trade Organization was established in the 1990s, superseding the GATT and providing a stronger institutional foundation for international trading arrangement among countries. As an international organization it faces a number of challenges, including achieving agreement over trade in services, bringing in new members from the economies in transition and developing countries, making the strengthened dispute settlement mechanism effective, and bringing about an increasingly open multilateral trading system. This volume analyzes the challenges and opportunities confronting the WTO. Several chapters address the WTO's institutional capacity directly, through such issues as the way national policies may influence or constrain the WTO, the difficulties of achieving coherence with the World Bank and the IMF, and the resources available to the WTO's secretariat in relation to the tasks it faces. Other papers in this volume consider more contemporary policy issues facing the WTO, including how to bring services trade into an open multilateral framework, how dispute settlement mechanisms can be improved, and how other concerns, such as labour standards and environmental issues may be addressed. Two papers focus on the WTO's relationship to developing countries and countries in transition, and an introductory chapter provides an overview of the WTO's operation. The text presumes no technical background in economics.
Keywords: World trade organization